재정지출의 시점 간 재원배분 조정에 따른 경기조절 효과성에 관한 연구 - 김성태 (13063, 2013)
Now that fiscal soundness is increasingly important influenced by the euro area fiscal crisis, early budget execution has been under the spotlight as a tool for economy control, other than typical expansionary method, such as supplementary budget. Basical